Comparative chromosome mapping of repetitive sequences. Implications for genomic evolution in the fish, Hoplias malabaricus - Bertollo Luiz AC; Martins Cesar; Cioffi Marcelo B (BMC Genetics, 2009)
Abstract Background Seven karyomorphs of the fish, Hoplias malabaricus (A-G) were previously included in two major groups, Group I (A, B, C, D) and Group II (E, F, G), based on their similar karyotype structure. In this paper, karyomorphs from Group I were analyzed by means of distinct chromosomal markers, including silver-stained nucleolar organizer regions (Ag-NORs) and chromosomal location of repetitive sequences (18S and 5S rDNA, and satellite 5SHindIII-DNA), through fluorescence in situ hybridization (FISH), in order to evaluate the evolutionary relationships among them. Results The results showed that several chromosomal markers had conserved location in the four karyomorphs. In addition, some other markers were only conserved in corresponding chromosomes of karyomorphs A-B and C-D. These data therefore reinforced and confirmed the proposed grouping of karyomorphs A-D in Group I and highlight a closer relationship between karyomorphs A-B and C-D. Moreover, the mapping pattern of some markers on some autosomes and on the chromosomes of the XY and X1X2Y systems provided new evidence concerning the possible origin of the sex chromosomes. Conclusion The in situ investigation of repetitive DNA sequences adds new informative characters useful in comparative genomics at chromosomal level and provides insights into the evolutionary relationships among Hoplias malabaricus karyomorphs.